Mast cell biology contemporary and emerging topics - Gilfillan, Alasdair M.; Metcalfe, Dean D. (Advances in Experimental Medicine and Biology, 2011)
The editors of Mast Cell Biology, Drs. Gilfillan and Metcalfe, have enlisted an outstanding group of investigators to discuss the emerging concepts in mast cell biology with respect to development of these cells, their homeostasis, their activation, as well as their roles in maintaining health on the one hand and on the other, their participation in disease.